2012
DOI: 10.1016/j.mayocp.2012.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mastoscopic and Conventional Axillary Lymph Node Dissection in Breast Cancer: Long-term Results From a Randomized, Multicenter Trial

Abstract: Objective: To compare the long-term results of mastoscopic axillary lymph node dissection (MALND) and conventional axillary lymph node dissection (CALND). Patients and Methods: From January 1, 2003, through December 31, 2005, a group of 1027 consecutive patients with operable breast cancer were randomly assigned to 1 of 2 study groups: MALND and CALND. The median follow-up was 63 months. The primary end points of the study were operative outcomes, complication reduction, function conservation, and cosmetics. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 40 publications
1
40
0
2
Order By: Relevance
“…The distribution of patients for 996 patients nally evaluable between MALND group and CALND group according to age, histologic, tumor grade, estrogen-receptor, proliferation rate and peritumoral vascular invasion was similar, reported previously. 7 The nal cohort of 996 patients was followed for an average of 184 months (range,164 to 191 months) during which time. The patients' outcomes at 15 years are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The distribution of patients for 996 patients nally evaluable between MALND group and CALND group according to age, histologic, tumor grade, estrogen-receptor, proliferation rate and peritumoral vascular invasion was similar, reported previously. 7 The nal cohort of 996 patients was followed for an average of 184 months (range,164 to 191 months) during which time. The patients' outcomes at 15 years are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The protocol was approved by institutional review board committees of all institutions in compliance with the Declaration of Helsinki and guidelines for good clinical practice. 7 To be included in study, patients had to have no axillary lymph node disease on preoperative clinical examination or lymph nodes less than 1 cm by color ultrasonic inspection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that mastoscopic sentinel lymph node biopsy (MSLNB) has similar disease-free survival and overall-survival to that of conventional ALND, but it can reduce postoperative complications and enhance aesthetic appearance of the axilla [9]. Compared to conventional approaches, surgeries in conjunction with endoscopic techniques are minimally invasive, thereby restricting scars.…”
Section: Introductionmentioning
confidence: 99%